METROPOLIS MANAGEMENT: RUSSIAN AND INTERNATIONAL PRACTICE IN WASTE MANAGEMENT REGULATION - Miloradov, Konstantin; Vrazhnov, Aleksey; Chelyapina, Olga; Sekerin, Vladimir; Gorokhova, Anna (Revista Inclusiones, 2020)
The article presents the issues of organizational and legal maintenance of waste management in large cities. Today the problem of municipal and commercial waste becomes especially important; particularly, it concerns large cities ― metropolises. The objective of this study is a systematic analysis of waste management in large cities with the identification of problems and the proposal of organizational and legal mechanisms to solve them. The topical issues of removal and recycling of municipal solid waste are considered in the article. Systems of collection and transport support used for transportation of domestic and industrial waste, as well as subsequent recycling and processing, are analyzed. Examples of Russian and global experience in creating and operating such systems are presented. It is concluded that the system of waste management in metropolises of the Russian Federation, according to many indicators, does not meet the requirements adopted in developed countries and needs to be improved, both in technical terms and in organizational and legal support. The authors have proposed several regulatory and legal measures for large-scale technical reequipment and development of a fundamentally new attitude to the environment among the population, primarily in large cities. These measures include, along with bans and regulations, economic incentives for the organization of modern waste collection methods. The results of the study can be used as a recommendation to the legislative bodies of the constituent entities of the Russian Federation ― metropolises and municipalities in large cities, their administrations, and business representatives in the field of waste management, as well as elements of environmental education of metropolis citizens.